Adaptive arbitration of aerial swarm interactions through a Gaussian kernel for coherent group motion - Manoni, Tiziano; Albani, Dario; Horyna, Jiri; Petracek, Pavel; Saska, Martin; Ferrante, Eliseo (Frontiers in Robotics and AI, 2022)
Swarm behaviors offer scalability and robustness to failure through decentralized and distributed design. When designing coherent group motion as in swarm flocking, virtual potential functions are a widely used mechanism to ensure the above properties. However, arbitrating through different virtual potential sources in real-time has proven to be difficult. Such arbitration is often affected by fine-tuning of the control parameters used to select among the different sources, and by manually set cut-offs used to achieve a balance between stability and velocity. A reliance on parameter tuning making these methods not ideal for field operations of aerial drones which are characterized by fast non-linear dynamics hindering the stability of potential functions designed for slower dynamics. A situation that is furthermore exacerbated by parameters that are fine tuned in the lab, often not appropriate to achieve satisfying performances on the field. In this work, we investigate the problem of dynamic tuning of local interactions in a swarm of aerial vehicles with the objective of tackling the stability-velocity trade-off. We let the focal agent autonomously and adaptively decide which source of local information to prioritize and at which degree---e.g., which neighbor interaction or the goal direction. The main novelty of the proposed method lies in a Gaussian Kernel used to regulate the importance of each element in the swarm scheme. Each agent in the swarm relies on such mechanism at every algorithmic iteration and uses it to tune the final output velocities. We show that the presented approach can achieve cohesive flocking while at the same time navigating through a set of way-points at speed. In addition, the proposed method also allows to achieve other desired field properties such as automatic group splitting and joining over long distances. The above properties have been empirically proven by an extensive set of simulated and field experiments, in communication-full and communication-less scenarios. Moreover, the presented approach has been proven to be robust to failures, intermittent communication, and noisy perceptions.